2019
DOI: 10.1016/j.carbon.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermoelectric power of melt mixed vapor grown carbon nanofiber polypropylene composites

Abstract: In this work, commercial vapor grown carbon nanofibers (CNF), produced by chemical vapor deposition (CVD), were melt extruded with polypropylene (PP) with the aim of analyzing their thermoelectric properties (i.e., electrical conductivity, thermoelectric power, power factor and figure of merit). Unexpectedly, all PP/CNF composites, instead of showing the typical positive thermoelectric powers (TEP) observed for this type of carbon-based polymer composites, they showed negative TEP values.These results can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
4
20
2
Order By: Relevance
“…Organic thermoelectric materials have been suggested as alternatives 8,9 alongside carbon materials 10 and composites of the two. 11,12 These materials have demonstrated decent power factors 9,11 and offer scalable processing by printing and other techniques, though ZT values are still well below unity.…”
Section: Introductionmentioning
confidence: 99%
“…Organic thermoelectric materials have been suggested as alternatives 8,9 alongside carbon materials 10 and composites of the two. 11,12 These materials have demonstrated decent power factors 9,11 and offer scalable processing by printing and other techniques, though ZT values are still well below unity.…”
Section: Introductionmentioning
confidence: 99%
“…By using PP based p-and n-type composites, they were able to prepare a demonstrator of a TE generator, which generated with 49 leg pairs a thermovoltage of 110 mV at 70 K temperature difference. Another way to generate n-type PP composites was described recently by Paleo et al [45], who incorporated 1 to 5 wt% carbon nanofibers into a PP matrix and reported Seebeck coefficients of about −8.5 µV/K.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for pristine SWCNT films, positive S-values are reported, e.g., by Nonoguchi et al [14] with 49 µV/K and Piao et al [15] with 39 µV/K (SWCNT from Thomas Swan Co. LTD, Consett, UK). Only recently a study by Paleo et al [16] reported a negative Seebeck coefficient for melt mixed composites based on PP in which the filler was an industrial high temperature treated carbon nanofiber (CNF) and no additives were added. Seebeck coefficients up to −8.5 µV/K (at 2.4 vol % loading) were reported.…”
Section: Introductionmentioning
confidence: 99%